Perspective: causes and functional significance of temporal variations in attention control - Lenartowicz, Agatha; Simpson, Gregory V.; Cohen, Mark S. (Frontiers in Human Neuroscience, 2013)
Attention control describes the human ability to selectively modulate the plethora of sensory signals and internal thoughts. The neural systems of attention control have been extensively studied, warranted by the importance of this ability to daily functioning. In the present perspective we consider an emerging theme in the study of attention control – slow temporal fluctuations. We posit that these fluctuations are functionally significant and may reflect underlying interactions between the neural systems related to attention control. We explore thought experiments to generate different perspectives on landscapes created by the interactions between attention control networks and the sources of input to these control systems. We examine interactions of the FPN and the default mode network in the context of internal cognition and the noradrenergic modulatory projections in the context of arousal, and consider the implications of these inter-network dynamics on attention states and attention disorders. Through these thought experiments we hope to highlight the breadth of potential knowledge to be gained from the study of slow fluctuations in attention control.